TIcaGrEloR and Absorb bioresorbable vascular scaffold implantation for recovery of vascular function after successful chronic total occlusion recanalization (TIGER‐BVS trial): Rationale and study design. Issue 1 (14th July 2017) - Brugaletta, Salvatore; Gomez‐Lara, Josep; Caballero, Juan; Ortega‐Paz, Luis; Teruel, Luis; Jimenez Fernandez, Miriam; Romaguera, Rafael; Alcalde Martinez, Vicente; Ñato, Marcos; Molina Navarro, Eduardo; Gomez‐Hospital, Joan‐Antoni; Correa Vilches, Concepcion; et al.
Abstract: Objectives: To explore the role of ticagrelor versus clopidogrel in coronary blood flow normalization immediately after chronic coronary total occlusion (CTO) recanalization. Background: Coronary vascular function of a CTO immediately after recanalization is demonstrated to be poor. Methods: The TIGER BVS is a prospective, double‐randomized, open‐label, two parallel‐group controlled clinical trial to evaluate efficacy of ticagrelor versus clopidogrel in improving vascular function of coronary segment distal to CTO immediately after CTO recanalization. A total of 50 patients who receive CTO PCI will be randomized 1:1 to receive ticagrelor versus clopidogrel at least 3 days before the procedure. Immediately after CTO recanalization with Absorb BVS implantation, a specific study of vascular function under adenosine infusion will be performed. Patients will be therefore randomized 1:1 to receive angiographic follow‐up with vascular function and optical coherence tomography analyses at 1‐ or 3‐year follow‐up. This study is registered onClinicalTrials.gov with number NCT02211066. Conclusions: The TIGER BVS trial will provide the first randomized comparison between ticagrelor versus clopidogrel in recovering vascular function in CTO patients. It will also provide important data on vascular restoration therapy of Absorb BVS in this scenario.